Intra- and Interspecies Transmission of Atypical BSE − What Can We Learn from It? - Balkema-Buschmann, Anne (Food Saf (Tokyo), 2016)
After the detection of the first cases of atypical bovine spongiform encephalopathy (BSE) more than ten years ago, the etiology, pathogenesis and agent distribution of these novel BSE forms in cattle were completely unknown. Many studies have been performed in the meantime to elucidate the pathogenic mechanisms of these diseases. A wealth of data has been accumulated regarding the distribution of the abnormal isoform of the prion protein, PrP(Sc), in tissues of affected cattle, confirming the general restriction of the PrP(Sc) and agent distribution to the central and peripheral nervous system, albeit at slightly higher levels as compared to classical BSE. However, due to lack of data, the assumptions regarding the spontaneous etiology of both atypical BSE forms (H-BSE and L-BSE) and also the origin of the classical BSE epidemic are still mainly speculative. By performing subpassage experiments of both the atypical BSE forms in a variety of conventional and transgenic mice and Syrian Gold hamsters, we aimed to improve our understanding of the strain stability of these BSE forms. It turned out that under these experimental conditions, both the atypical BSE forms may alter their phenotypes and become indistinguishable from classical BSE. Information about the classical and atypical BSE strain characteristics help to improve our understanding of the correlation between all three BSE forms.